2017
DOI: 10.1021/acs.nanolett.7b02694
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically-Driven Phase Transformation during Lithiation in Copper Sulfide Nanoflakes

Abstract: Two-dimensional (2D) transition metal chalcogenides have been widely studied and utilized as electrode materials for lithium ion batteries due to their unique layered structures to accommodate reversible lithium insertion. Real-time observation and mechanistic understanding of the phase transformations during lithiation of these materials are critically important for improving battery performance by controlling structures and reaction pathways. Here, we use in situ transmission electron microscopy methods to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 63 publications
6
73
1
Order By: Relevance
“…To confirm this, XRD and SEM were used to characterize intermediate charge products. [29]. After the 10th and 20th discharge, however, the Li 2 S product became very evident.…”
Section: Electrochemistry Of Cu 2 Smentioning
confidence: 95%
See 2 more Smart Citations
“…To confirm this, XRD and SEM were used to characterize intermediate charge products. [29]. After the 10th and 20th discharge, however, the Li 2 S product became very evident.…”
Section: Electrochemistry Of Cu 2 Smentioning
confidence: 95%
“…The CuS nanoflakes are hexagonal with thicknesses between 5 and 20 nm and basal plane 200 nm. Using an in situ STEM setup (Figure 5b), He et al [29] revealed that there was no formation of intermediate Cu 2-x S phases during lithiation of CuS nanoflakes. Using an in situ STEM setup (Figure 5b), He et al [29] revealed that there was no formation of intermediate Cu 2-x S phases during lithiation of CuS nanoflakes.…”
Section: Possible Reasons Underlying the Conflictsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,14] Also, the high-resolution Cu 2p XPS spectra of the pristine CuNWs-GN/PI/ LLZO separator ( Figure S20, Supporting Information) shows the signals of partial copper oxides and metallic copper. [24,25] Based on these above results, the metallic copper nanowires are highly reactive toward soluble polysulfide species, which can be transformed to copper sulfide compounds as schematically shown in Figure 4. [21] It is clear that the Li 1s of polysulfide treated CuNWs-GN/PI/LLZO separator (Figure 3e) shows a single peak at around 54.6 eV, which is 1.7 eV lower than that of the pristine Li 2 S 6 according to previous literature.…”
Section: Functionalities Of the As-designed Separatorsmentioning
confidence: 96%
“…It is believed that suitable cathode materials could be well widened if a conversion mechanism is introduced into Mg batteries. As Mg 2+ is a harder acid than Li + , a softer base such as S 2− or Se 2− ions should be more advantageous to construct the cathode in light of the kinetics . In this work, a Cu 9 S 5 nanoflower with a hierarchical structure is prepared and used as the cathode for Mg batteries.…”
Section: Introductionmentioning
confidence: 99%